A Review of Non-Thermal Plasma Technology: A novel solution for CO2 conversion and utilization. (January 2021) - George, Adwek; Shen, Boxiong; Craven, Michael; Wang, Yaolin; Kang, Dongrui; Wu, Chunfei; Tu, Xin
Abstract: Increasing attention has been drawn to carbon dioxide (CO2 ) conversion into higher-value platform chemicals and synthetic fuels due to global warming. These reactions require a large amount of thermal energy in order to proceed, which is ascribable to the high stability of the bonds in CO2 . Non-thermal plasma (NTP)-catalytic CO2 conversion has emerged as a promising method to significantly reduce the reaction temperature as plasma can activate CO2 at as low as room temperature and atmosphere pressure. However, this technology requires a paradigm shift in process design to enhance plasma-catalytic performance. CO2 conversion using plasma-catalysis has great potential to increase reaction efficiencies due to the synergetic effects between the plasma and catalysts. It is crucial to present the recent progress in CO2 conversion and utilization whilst providing a research prospects framework and direction for future research in both industries and laboratories. Herein, a comprehensive review of recent, encouraging research achievements in CO2 conversion using NTP is provided. The topics reviewed in this work are: i) the recent progress in different NTP sources in relation to product selectivity, conversion, and energy efficiency; ii) plasma-based CO2 reactions and applications; iii) CO2 conversion integrated with CO2 capture; and iv) current challenges and future perspectives. The high market value of the possible products from this process, including chemicals and fuels, make commercialization of the process feasible. Furthermore, the selectivities of these products can be further improved by developing suitable catalysts with effective sensitivities and performances under the intricate conditions needed to make these products. There is an urgent need for further studies to be performed in this emerging field. Highlights: Non-thermal plasma is an emerging and promising technology for the conversion of CO2 . Current technology development on CO2 capture and conversion has been reviewed. Plasma catalysis has great potential to generate a synergistic effect and enhance the selectivity of target products.